An Appraisal of Muon Neutrino Disappearance at Short Baseline. (20th November 2013) - Stanco, L.; Dusini, S.; Longhin, A.; Bertolin, A.; Laveder, M.
Abstract : Neutrino physics is nowadays receiving more and more attention as a possible source of information for the long-standing problem of new physics beyond the Standard Model. The recent measurement of the third mixing angle θ 13 in the standard mixing oscillation scenario encourages us to pursue the still missing results on leptonic CP violation and absolute neutrino masses. However, several puzzling measurements exist which deserve an exhaustive evaluation. We will illustrate the present status of the muon disappearance measurements at small L / E and the current CERN project to revitalize the neutrino field in Europe with emphasis on the search for sterile neutrinos. We will then illustrate the achievements that a double muon spectrometer can make with regard to discovery of new neutrino states, using a newly developed analysis.